Effective Transfer Entropy Approach to Information Flow Among EPU, Investor Sentiment and Stock Market - Yao, Can-Zhong; Li, Hong-Yu (Frontiers in Physics, 2020)
In contrast to the traditional view that economic policy affects investor sentiment and eventually causes stock price fluctuations, we reveal that investor sentiment is a reflection of both economic policy and stock market information. This article first proposes an improved ETE method with a sliding window. We verify that this new method can capture the dynamic orders effectively by validating this method with the linear TE method. Furthermore, using the improved method, we investigate the strength and direction of information flow among economic policy uncertainty (EPU), investor sentiment and stock market by the novel concept of dynamic effective transfer entropy. The EPU and investor sentiment results show that EPU influenced investor sentiment mainly from August 2015 to June 2016. Among different policies, China's exchange rate reform policy and “circuit-breaker” policy in the stock market played an important role. Moreover, the analysis of sentiment and stock price returns shows that investor sentiment is more a reflection of changes in stock price returns with a 1-month lag order and that the stock market has a significant bargainer effect and a weaker bandwagon effect. Finally, there is no significant information flow transmission relationship between EPU and stock market volatility, indicating that stock market fluctuations are essentially not affected by national policy fluctuations. Although investor sentiment is affected by changes, such as exchange rate reform and stock market policies, many investors do not form consensus expectations.